The carbon diaries 2015 - Lloyd, Saci. (New York : Holiday House, 2009)
In 2015, when England becomes the first nation to introduce carbon dioxide rationing in a drastic bid to combat climate change, sixteen-year-old Laura documents the first year of rationing as her family spirals out of control.
Includes bibliographical references (p. 330).
Book Links (A.L.A.).
Booklist starred.
School Library Journal starred.
Young Adult
Keywords: Climatic changes -- Juvenile fiction; Energy conservation -- Juvenile fiction; Families -- Juvenile fiction; Rationing -- Juvenile fiction; Climatic changes -- Fiction; Diaries -- Fiction; Energy conservation -- Fiction; Family life -- Fiction; Rationing -- Fiction; Climate -- Fiction; Consumption (Economics) -- Fiction; Diaries -- Fiction; Energy conservation -- Fiction; Family life -- Fiction; England -- Juvenile fiction; England -- Fiction; England -- Fiction